Soil attributes and crops productivity: changes due to the long time use of animal manure (Agroindustrial Science, 2022)
Animal manure may be used as a nutrient source for annual and perennial crops and pastures, promoting nutrient cycling and reducing costs with mineral fertilizers acquisition. Additionally, they are expected over the years to modify soil chemical, physical, and biological attributes. This review addresses the effect of animal manure applications on the soil-plant interface, emphasizing the following aspects: (a) animal manure characteristics that affect soil attributes, (b) changes in chemical, physical, and biological attributes of soils with a history of animal manure applications, and (c) effect of animal manure application on crop biomass production and yield. Changes on soil attributes depends on the animal manure and pedoclimatic characteristics. Animal manure applications in soil associated with mineral manure increase soil organic carbon and crop yield. Aggregates, density and water infiltration are favored by applying animal manure with high C:N. Macrofauna, microbial and biological activity increase with animal manure application. Finally, yield increases do not always accompany the improvement of all soil attributes. The effects of animal manure application on soil quality are more pronounced when carried out in an integrated manner with other soil management and conservation strategies.
Keywords: swine and cattle manure; soil organic carbon; soil aggregation; biological activity; grain crops